Prevalence of noise-induced hearing loss and the efficacy of a targeted intervention method to promote the use of hearing protection devices among palm oil mill workers in Pahang - Ramzan, Muhammad Sirri 'Ammar (2022)
Background Noise-induced hearing loss (NIHL) is the most commonly reported occupational disease in Malaysia. However, there is limited data on the prevalence of this disease across different occupational sectors. The palm oil industry is one of the main contributors to the nation’s economic growth. Crude palm oil production involves heavy machinery that poses considerable noise hazards to the workers. The introduction of the Occupational Safety and Health (Noise Exposure) Regulations 2019 was a positive step towards providing more comprehensive protection for workers’ hearing health. Employers are now required to take preventive actions at a lower daily noise exposure level of 82 dB(A) instead of 85 dB(A). Nonetheless, the use of hearing protection devices (HPD) remains a crucial component in preserving the hearing health of noise-exposed workers. Previous research on this topic has generally shown a low compliance level to HPD among local workers. Objectives This study aimed to determine the prevalence of NIHL and the efficacy of a targeted intervention to improve the use of HPD among palm oil mill workers in Pahang. Methodology Part One of this study was a cross-sectional study using existing screening audiometric data of palm oil mill workers in Pahang. The workers were categorized into low, moderate, and high exposure groups based on their workstation noise levels. Their audiograms were analysed to determine the prevalence of NIHL, defined as bilateral high-frequency hearing loss (3000 Hz to 6000 Hz) with or without an audiometric notch. Multiple logistic regression was used to determine the factors associated with NIHL. Part Two of this study was a quasi-experimental study involving noise-exposed workers from two palm oil mills. A translated and validated questionnaire was used to assess the determinants of HPD use among the workers. The intervention group received a targeted training module, while the control group received a standard employer-provided training module. Comparisons were made on the effect of different training modules on the workers’ self-reported HPD use and the intention to use HPD. Statistical analysis was conducted using paired t-test and repeated measure analysis of variance (ANOVA). Results The overall NIHL prevalence was 50.8%. Noise exposure level and age were significant predictors of NIHL among the workers. The risk of developing NIHL was high even for workers exposed to occupational noise levels below the noise exposure limit. The targeted training module was shown to have significantly improved HPD use from 60.7% to 77% after four months post-training. The workers’ intention to use HPD also increased significantly from 77.3% to 89.3%. On the contrary, there was no significant difference in HPD use or intention to use HPD among workers in the control group. Conclusion The findings showed a high prevalence of NIHL among palm oil mill workers, emphasizing the importance of a precautionary approach in protecting them from occupational noise hazards. This study also demonstrated the efficacy of a targeted intervention in improving compliance to HPD among noise-exposed workers. Overall, there is a need for more effective measures to conserve the hearing health of workers in this industry.